Hutterite‐type cataract maps to chromosome 6p21.32‐p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. Issue 1 (14th November 2015) - Boone, Philip M.; Yuan, Bo; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga‐Jauregui, Claudia; Jain, Mahim; Murdock, Todd J.; White, Janson J.; Jhangiani, Shalini N.; Walker, Kimberly; Wang, Qiaoyan; et al.
Abstract: Background: Juvenile‐onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. Methods: We performed whole exome sequencing of three Hutterite‐type cataract trios and follow‐up genotyping and mapping in four extended kindreds. Results: Trio exomes enabled genome‐wide autozygosity mapping, which localized the disease gene to a 9.5‐Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile‐onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP‐based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5‐ to 2.9‐Mb subregion (6p21.32‐p21.31) containing LEMD2 but not MUC21 . LEMD2 is expressed in mouse and human lenses and encodes a LEM domain‐containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). Conclusion: We performed a genetic and genomic study of Hutterite‐type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2 . Abstract : We mapped autosomal recessive Hutterite‐type cataracts to chromosome 6p21.32‐p21.31. We identified a predicted damaging mutation in LEMD2 (c.T38G) that segregates with the phenotype in extended Hutterite kindreds (LOD = 9.62), suggesting that LEMD2 is the disease gene for this condition. Furthermore, we identified a novel association of Hutterite‐type cataracts with sudden cardiac death at a young age.